2009
DOI: 10.1108/17549450200900030
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the ‘success’ of telehealth interventions

Abstract: Despite substantial investment over recent years in telehealth there appears to be little consensus regarding what a successful implementation should achieve. However, defining success is often controversial and complex due to differing views from the large number of stakeholders involved, the local environment where telehealth is deployed and the scope, or size, of any planned initiative. Nevertheless, a number of generic measures are proposed in this paper which then provides a framework for the measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Moreover, the increasing healthcare cost associated with aging creates diverse market opportunities for Telehealth (DelliFraine, & Dansky, 2008). While Telehealth has attracted considerable attention from healthcare providers in developed counties (Milligan et al, 2011;Brownsell, 2009), the ''least developed countries'' could perhaps benefit most from such technologies (Chanda & Shaw, 2010). Much of the world's elderly population (70%) resides in developing countries, and continues to rise at a rapid pace (WHO, 2002).…”
mentioning
confidence: 98%
“…Moreover, the increasing healthcare cost associated with aging creates diverse market opportunities for Telehealth (DelliFraine, & Dansky, 2008). While Telehealth has attracted considerable attention from healthcare providers in developed counties (Milligan et al, 2011;Brownsell, 2009), the ''least developed countries'' could perhaps benefit most from such technologies (Chanda & Shaw, 2010). Much of the world's elderly population (70%) resides in developing countries, and continues to rise at a rapid pace (WHO, 2002).…”
mentioning
confidence: 98%
“…including the punctual, professional, and personalized service provided by the service provider [18]. Brownsell [19] argued that care providers' engagement is one of prerequisites for telehealth success. Thus, care providers' support was also integrated into service quality measurement in this study, including professional and empathic attitude toward residents.…”
Section: Dandm Is Success Modelmentioning
confidence: 99%
“…This, together with the relative dearth of dementia-specific studies in ATT, means that a significant gap remains in our evidence. Although there are relatively large numbers of qualitative studies, audits and service evaluations, there are few studies with sufficient rigour and appropriate design to offer any degree of generalisability [ 15 ] or agreement about how ‘success’ can be measured [ 28 ]. One study has suggested that, when used appropriately, ATT is highly cost-effective.…”
Section: Introductionmentioning
confidence: 99%